Analysis of gastronomic events: a case study of Portugal - Kharenko, Dmytro; Dyshkantiuk, Oksana; Ivychuk, Liliia (Technology audit and production reserves, 2017)
The object of research was examination of the extent to which experience design contributes to the overall visitor experience at the traditional gastronomic festivals in Minho (Portugal). The Portugal traditional gastronomic festivals as well as culture are rich and diverse. But the results imply that the ability of these events to attract tourists from other regions and countries is not signiﬁcant, since the majority of visitors are locals. There is a need to attract new tourist segments, but it is difficult to do using ineffective event design. The festivals need to create a more holistic experience that can attract more visitors each year. The survey based in a quantitative approach was developed and applied in the festival. This instrument provided important insights on the effectiveness of the strategy applied in the organization. A total of 232 valid questionnaires were applied, aimed to understand who the visitors are, their needs, behavior, feelings towards to the festival. Because it is very important to have this information to adapt the event in order to be competitive in the market. The results of this research suggest that the traditional gastronomic festivals have great development potential, if it makes the necessary adjustments needed to exceed customers’ expectations by developing unique experiences that engage visitors. Along with this information, recommendations for improvement of the festivals, which derived from the analysis undertaken, were presented. In preparing future editions of the events, the organizers should redesign their approach, taking into consideration the current and emerging tourism trends.